Health-Related Quality Of Life, Uncertainty, ‎and Anxiety among Patients with Chronic Obstructive Pulmonary Disease [version 1; peer review: 2 approved] - Nazih Abu Tabar (F1000 Research Ltd, 2021)
Patients’ with Chronic Obstructive Pulmonary Disease suffer from serious respiratory symptoms that increase anxiety, stress, and uncertainty, and affect quality of life. The aim of this study was to assess level of anxiety, uncertainty, and health related quality of life (HRQoL) among COPD patients in Jordan. Correlational cross-sectional survey design was used to collect data from 153 COPD patients. ‎The study was conducted at pulmonary clinics in three major referral hospitals in Jordan that provide care for COPD patients from different parts of the country. To assess HRQoL, St. George ‎Respiratory Questionnaire‎ was completed. Uncertainty and anxiety level was measured by Mishel's uncertainty of illness scale and state anxiety inventory respectively. The mean age of participants was 66.8 (SD= 10.3) and most participants were males (94.1%) with. The mean score of HRQoL was 57.9 (SD = 20.5). The mean score of participants’ level of anxiety was 38.1 (SD = 11.1). The mean score of uncertainty was 66.1 (SD= 11.1). There is a statistically significant positive relationship between HRQoL and anxiety (r =.433, p< .01), and uncertainty (r=.483, p<.01). Increased anxiety and uncertainty among COPD patients was associated with low HRQoL. Health care providers need to pay attention the effect of anxiety and uncertainty on COPD patients’ quality of life and institute appropriate management.